2015
DOI: 10.17241/smr.2015.6.2.54
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Mass Presenting as Obstructive Sleep Apnea Syndrome

Abstract: Background and ObjectiveaaThe aim of this study was to analyze the clinical symptoms, physical examinations, imaging studies, polysomnographic evaluations, and pathologic findings of patients with a nasal mass presenting as obstructive sleep apnea syndrome (OSAS).MethodsaaThe study population consisted of adult OSAS patients who had a nasal mass and were successfully treated by nasal surgery alone. In this study, we analyzed clinical symptoms, physical examinations, imaging studies, pre and postoperative polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Nasal surgery included inferior turbinate reduction, septal surgery, valve surgical correction, and endoscopic sinus surgery. Many studies have reported investigation of the effect of isolated nasal surgery on OSA [12][13][14][15]. According to a study published in Korea, nasal surgery alone can be a useful option for improving such symptoms as excessive daytime sleepiness, sleep inefficiency, and snoring in OSA patients with nasal obstruction [12].…”
Section: Nasal Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal surgery included inferior turbinate reduction, septal surgery, valve surgical correction, and endoscopic sinus surgery. Many studies have reported investigation of the effect of isolated nasal surgery on OSA [12][13][14][15]. According to a study published in Korea, nasal surgery alone can be a useful option for improving such symptoms as excessive daytime sleepiness, sleep inefficiency, and snoring in OSA patients with nasal obstruction [12].…”
Section: Nasal Surgerymentioning
confidence: 99%
“…Although isolated nasal surgery has a relatively low success rate for OSA, it can be very effective for OSA patients who have surgically correctable anatomical abnormalities. Lee et al [13] indicated that nasal surgery alone may be efficient for the alleviation of minimum oxygen saturation and respiratory events, including apnea and hypopnea, in OSA patients with large nasal masses. Park et al [14] also suggested that isolated nasal surgery may improve not only polysomnography-related parameters but also PAP-related parameters, such as optimal level of PAP and PAP adherence.…”
Section: Nasal Surgerymentioning
confidence: 99%